2017
DOI: 10.4028/www.scientific.net/kem.758.166
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Sodium-Substituted Hydroxyapatite Ceramics via Ultrasonic Spray-Pyrolysis Route and their Material Properties

Abstract: Biological apatite presented in bone and teeth of mammals contains various ions in trace levels. Substitution of the ions into hydroxyapatite (HAp) can ensure higher bioactivity compared with stoichiometric HAp. It is known that sodium (Na) has been detected as an abundant trace element next to the presence of calcium and phosphorous in natural bone. The aim of this study is to examine the effect of substitution of Na on material properties of the HAp ceramics. Therefore, we have synthesized the sodium-substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In our previous study focused on cation doping, Yokota et al [9,10] fabricated sodium-or potassiumsubstituted HAp. They have also successfully fabricated bone HAp ceramics, including bone minerals with six types of ions; Na + , K + , Mg 2+ , F − , Cl − and CO 3 2− .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study focused on cation doping, Yokota et al [9,10] fabricated sodium-or potassiumsubstituted HAp. They have also successfully fabricated bone HAp ceramics, including bone minerals with six types of ions; Na + , K + , Mg 2+ , F − , Cl − and CO 3 2− .…”
Section: Introductionmentioning
confidence: 99%
“…As described above, a number of studies have reported the effects of cations in biological apatite [3][4][5][6][7][8][9][10][11]. An artificially obtained material may have promoted bioactivity by the effect of substituted ions; for example, magnesium ions promote bone formation [14].…”
Section: Introductionmentioning
confidence: 99%
“…As compared to HA and Eu:HA NPs at 550 °C, the lattice constants (Supporting Information, Table S3) of the Eu:HA-F- 550 and Cit/Eu:HA-F- 550 NPs decreased in the a -axis direction and increased in the c -axis direction. For the Eu:HA-F- 550 NPs, it was speculated that the Na + and CO 3 2– ions substituted for Ca and PO 4 sites, respectively, so that the a -axis decreased and the c -axis increased . For the Cit/Eu:HA-F- 550 NPs, the OH site was substituted with F – ions to decrease the a -axis, in addition to the same mechanism to the Eu:HA-F- 550 NPs.…”
Section: Resultsmentioning
confidence: 99%
“…For the Eu:HA-F-550 NPs, it was speculated that the Na + and CO 3 2− ions substituted for Ca and PO 4 sites, respectively, so that the a-axis decreased and the c-axis increased. 50 For the Cit/Eu:HA-F-550 NPs, the OH site was substituted with F − ions to decrease the a-axis, 51 in addition to the same mechanism to the Eu:HA-F-550 NPs. S4 (Supporting Information) shows the FE-SEM images of the NPs, suggesting that the aggregates of primary NPs were observed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Various studies suggest that calcium phosphate nanoparticles can be successfully used as a fluorescent probe after doping with lanthanide [ 8 , 9 ]. The main methods used to obtain hydroxyapatite are: Conventional method [ 10 , 11 ], wet chemical synthesis [ 12 ], hydrothermal conversion of calcium carbonate [ 13 , 14 ], bone calcination [ 15 , 16 ], solid phase reactions [ 17 , 18 ], co-precipitation reactions [ 19 , 20 ], sol-gel method [ 21 , 22 , 23 ], biomimetic synthesis [ 24 , 25 ], and pyrolysis [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%